A Protoplast System for CRISPR-Cas Ribonucleoprotein Delivery in Pinus taeda and Abies fraseri - Barbara M. Marques; Daniel B. Sulis; Bethany Suarez; Chenmin Yang; Carlos Cofre-Vega; Robert D. Thomas; Justin G. A. Whitehill; Ross W. Whetten; Rodolphe Barrangou; Jack P. Wang (Plants)
Climate change profoundly impacts the health, productivity, and resilience of forest ecosystems and threatens the sustainability of forest products and wood-based industries. Innovations to enhance tree growth, development, and adaptation offer unprecedented opportunities to strengthen ecosystem resilience and mitigate the effects of climate change. Here, we established a method for protoplast isolation, purification, and CRISPR-Cas ribonucleoprotein (RNP) delivery in Pinus taeda and Abies fraseri as a step towards accelerating the genetic improvement of these coniferous tree species. In this system, purified protoplasts could be isolated from somatic embryos with up to 2 × 106 protoplasts/g of tissue and transfected with proteins and nucleotides, achieving delivery efficiencies up to 13.5%. The delivery of functional RNPs targeting phenylalanine ammonia lyase in P. taeda and phytoene desaturase in A. fraseri yielded gene editing efficiencies that reached 2.1% and 0.3%, respectively. This demonstration of RNP delivery for DNA-free genome editing in the protoplasts of P. taeda and A. fraseri illustrates the potential of CRISPR-Cas to enhance the traits of value in ecologically and economically important tree species. The editing system provides a foundation for future efforts to regenerate genome-edited forest trees to improve ecosystem health and natural resource sustainability.